Gated Community Potret Kesenjangan Sosial: Studi Kasus: Casa Grande Real Estate di Kabupaten Sleman, Provinsi Daerah Istimewa Yogyakarta - Hendy Thomi Noya; Wiyatiningsih (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2022)
Title: Gated Community A Portrait of Social Gaps. Case Study: Casa Grande Real Estate in Sleman Regency, Yogyakarta Special Region Province The rapid development of Yogyakarta affects the spread of housing areas to the region of Sleman Regency. Various types of housing overgrow. The middle-high accommodations are usually exclusive and surrounded by fences. The gated community has become a trend for the community’s privacy and security. A gated community's existence can potentially create social gaps between residents and local people. Based on the background, the study’s purpose of identifying social gaps caused by the gated community and the influencing architectural elements. The study implemented a qualitative research method with a case study approach comparing the case with other cases as the context. The study was done in Casa Grande real estate compared to Bale Hinggil and Pesona Merapi real estate. The three cases are in Sleman Regency, Yogyakarta Special Region Province. The study results show that the fences bordering the housing community strengthen the concept of “the others” as dangerous people that must be watched over. However, the development of social media changes the restricted relation into partnership relations. Social segregation that groups people according to economic class is shifting. However, a gated community still exists to meet modern society’s needs, lifestyle, privacy, comfort, and security.